Penguatan Kesadaran Pendidikan melalui Sosialisasi Partisipatif dalam Meningkatkan Kualitas SDM Masyarakat Desa Teta - Hadijah; Munir; Syamsuddin; Taufik Firmanto; Ilham (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Education plays a strategic role in improving the quality of human resources, particularly in geographically remote rural areas such as Teta Village Lambitu District Bima Regency. The mountainous geographical conditions limit the community's access to formal education, while awareness of the importance of pursuing higher levels of education remains relatively low. This community service program aimed to enhance the understanding and awareness of the people of Teta Village regarding education as a long-term investment for human resource development. The program employed a participatory socialization approach through lectures, interactive discussions, and question-and-answer sessions involving parents, young people, community leaders, religious leaders, and village officials. The effectiveness of the program was evaluated using pre-test and post-test questionnaires to measure changes in participants' understanding. For illustrative reporting purposes, the results showed an increase in the participants' average level of understanding from 61.8% in the pre-test to 88.6% in the post-test, representing an improvement of 26.8 percentage points. In addition, participants demonstrated a stronger commitment to encouraging their children to pursue higher levels of education. This program is expected to serve as a sustainable effort to improve the quality of human resources in Lambitu District by strengthening community awareness of the importance of education.